The Short and Long-Run Performance of Sharia-Compliant Initial Public Offerings (IPOs) in the Emerging Market: Evidence from the Saudi Arabia Share Market - Kamaludin, Kamilah; Zakaria, Nadisah (Journal of Reviews on Global Economics, 2019)
This study examines the short- and long-run share performance of 40 Sharia-compliant IPO companies listed on the Saudi Arabia Stock Exchange (Tadawul) from 1st January 2000 to 31st August 2017. This study employs both market-adjusted initial returns and buy-and-hold abnormal return to measure the share performance of IPOs. First, the analysis shows that Sharia-compliant IPOs are underpricing with abnormal initial returns of 79.23%. Second, the results suggest that investors could earn positive and significant market-adjusted BHAR of 14.67% if they held IPO shares over the eighteen-month period following the listing date when EWI is used as a market benchmark. This study also finds that IPO companies outperformed the VWI although the results are insignificant. The findings on the long-run overperformance contribute to the IPO literature on long-run performance of Sharia-compliant IPOs. The present study would benefit foreign investors and market regulators who are trying to understand the market behaviour in an emerging market.